2018
DOI: 10.1155/2018/1021969
|View full text |Cite
|
Sign up to set email alerts
|

Designs of Biomaterials and Microenvironments for Neuroengineering

Abstract: Recent clinical research on neuroengineering is primarily focused on biocompatible materials, which can be used to provide electroactive and topological cues, regulate the microenvironment, and perform other functions. Novel biomaterials for neuroengineering have been received much attention in the field of research, including graphene, photonic crystals, and organ-on-a-chip. Graphene, which has the advantage of high mechanical strength and chemical stability with the unique electrochemical performance for ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…The use of microtopographical patterns have been reported to promote the regeneration of peripheral nerves (Farrukh, Zhao, & del Campo, 2018; Gomez, Lee, Nickels, & Schmidt, 2007; Thomson et al, 2017; Y. Yang, Zhang, Chai, & Gu, 2018). During axonal regeneration, different cell types in the nerve undergo dynamic changes that are controlled by external cues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of microtopographical patterns have been reported to promote the regeneration of peripheral nerves (Farrukh, Zhao, & del Campo, 2018; Gomez, Lee, Nickels, & Schmidt, 2007; Thomson et al, 2017; Y. Yang, Zhang, Chai, & Gu, 2018). During axonal regeneration, different cell types in the nerve undergo dynamic changes that are controlled by external cues.…”
Section: Introductionmentioning
confidence: 99%
“…The use of microtopographical patterns have been reported to promote the regeneration of peripheral nerves (Farrukh, Zhao, & del Campo, 2018;Gomez, Lee, Nickels, & Schmidt, 2007;Thomson et al, 2017;Y. Yang, Zhang, Chai, & Gu, 2018).…”
mentioning
confidence: 99%
“…However, the mammals only have very limited HC regeneration ability; most of the damaged HCs cannot be spontaneously regenerated, which make the HC loss and hearing loss to be irreversible [58][59][60][61][62]. CIs are the most efficient clinical therapeutic devices for sensorineural deafness patients, and recent studies have shown that application of CI-based electric acoustic stimulation together with multiple biomaterials also can promote the differentiation of neural stem cell [63][64][65][66] and promote maturation of spiral ganglion neuron [67][68][69][70]. However, the neurophysiological study of musical pitch identification in CI users is still lacking in the hearing research field.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have shown that PDA-modified biomaterials can stimulate neurons and guide axonal extension even in the absence of some functions such as conductivity, topography, and microenvironment control. However, as Yang et al ( 2018 ) proposed, the existing studies have not considered adding such factors together to regulate NSC growth behavior and thus identify more efficient and economical methods for use in NTE. Therefore, the combination of a PDA functionalized scaffold and carbonized electrospun fiber with unique electrochemical properties might be a new strategy for the design of biomaterials and microenvironments for NTE.…”
Section: Introductionmentioning
confidence: 99%